(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
The ICT-readiness of extension agents involves assessing their familiarity, skills, availability. access and usage of technology tools that can enhance extension service deliveries. This study assessed the ICTs-Readiness of agricultural extension agents in Kwara State, Nigeria. One hundred and five Agricultural extension workers were randomly selected for the study. Description statistics such as frequency count, percentage and mean were used for the study. The result revealed that about 64.8% of the respondents had low level of usage of ICTs/Digital devices. About 86.7% of the extension agents were somewhat ready for the use of ICTs/digital devices for agricultural extension services. This study therefore recommends that there should be continuous training of extension agents on the various digital devices so as to enhance extension services deliveries to the farmers in the study area.